An Audit of Undescended Testis treated at DHQ Hospital Abbottabad (Medical Forum Monthly, 2024)
Background: Undescended testis or cryptorchidism which occurs in 2% of boys born at term, is one of the most common congenital abnormalities. Cryptorchidism is associated with impaired fertility and is a risk factor for testicular cancer. There is evidence that post natal germ cell development deteriorates in the undescended testis after the first year and perhaps for this reason, the risk of infertility increases with age. The question of whether the age at treatment has any effect on the risk of testicular cancer is controversial. Primary management of cryptorchidism is surgery which is usually performed in infancy. Study Design: A retrospective study. Place and Duration of Study: This study was conducted at DHQ Hospital Abbottabad from Oct 1998- Dec 2008. Patients and Methods: Total of 159 patients were treated during this period. Children of all ages were included. The patients were divided into different age groups. Patients were investigated with physical examination, ultrasonography, CT scan and MRI. All patients were treated with open surgical orchidopexy. Pre operative complications were evaluated. Patients were followed up and complications were noted. Results: The common age group was above 05 yrs 80 patients (50%).Rt side was involved in 82 cases(52%) and Lt side in 54 cases(34%). Inguinal hernia was the most common associated finding 76 cases(48%) with cryptorchidism. The results indicate that age at orchiopexy has an effect on the risk of testicular cancer in boys with an undescended testicle. The risk among those treated at 13 years of age or older was twice the risk among those who were treated at younger ages. Conclusions: Failure of the testicle to descend through the inguinal canal during the fetal life may be related to enough of a specific type of maternal hormones, failure of testis to respond to inadequate pull from the gubernaculum, or various other factors. Ultrasound can help to identify testicle located in the inguinal canal, but is of limited use for intra abdominal testis. MRI and CT scan can be useful for intra abdominal testis, but they are often difficult to use on small children and have a high rate of false negative results. Many men who were born with undescended testes have reduced fertility, even after orchiopexy in infancy. The most effective treatment is surgery which is usually performed in infancy. Hormonal treatment has the advantage of avoiding anesthesia and being minimally invasive. HCG is the drug of choice. However success rates have been reported to be as low as 10%. The principal major complication of all types of orchiopexy is loss of the blood supply to the testis, resulting in the loss of the testis due to ischemic atrophy or fibrosis.